(untitled) (Vietnam Journal of Community Medicine, 2025)
Introduction: Procalcitonin (PCT) is a valuable biomarker commonly used to diagnose and monitor infectious inflammation. Objective: To investigate serum procalcitonin concentrations in patients with positive blood culture sepsis and to evaluate the association between serum procalcitonin concentrations and isolated bacterial pathogens. Subjects and methods: A cross-sectional study of 278 patients diagnosed with sepsis at Thai Nguyen A Hospital from January to September 2024. Results: The median serum PCT concentration in the positive blood culture group (22.1 ng/ml) was higher than that in the negative blood culture group (8.32 ng/ml) with p<0.05. The area under the curve was 0.682 (p<0.01), and the cut-off point for distinguishing between positive and negative blood culture sepsis was 5.4 ng/ml, with a sensitivity of 54.8% and a specificity of 80.6%. The mean serum PCT concentration of the gram-negative group was 20.6 ng/ml, higher than that of the gram-positive group at 0.7 ng/ml, with p < 0.05. The area under the curve was 0.791 with p < 0.01. The cut-off point for distinguishing between gram-positive and gram-negative bacteremia was 9.16 ng/ml, with a sensitivity of 61% and a specificity of 76.2%. Conclusion: PCT is valuable in distinguishing between blood culture-positive and negative bacteremia and gram-negative and gram-positive bacteremia.